Study of clinical profile of Guillain-Barré syndrome in children upto 12 years during an epidemic outbreak - Gupta, Anuradha; Awadkhan, Manjunath; Kumbhojkar, Sangita; Jadhav, Maheshwari; Miraje, Bhushan (International Journal of Contemporary Pediatrics, 2025)
Guillain-Barré syndrome (GBS) is an acute inflammatory polyneuropathy and leading cause of Acute flaccid paralysis (AFP) in children. Outbreaks are often linked to infections, but regional data on paediatric GBS in India remains limited. To describe the clinical presentation of paediatric GBS cases admitted in RCSM GMC Kolhapur during an outbreak that occurred in Maharashtra, India in 2025. To correlate electrophysiological findings with clinical profile and outcomes of paediatric GBS cases admitted in RCSM GMC Kolhapur during an outbreak that occurred in Maharashtra, India in 2025. This is a descriptive observational case series of 5 children admitted with GBS during an outbreak. Cases were diagnosed using Brighton Collaboration criteria and nerve conduction velocity (NCV) studies. Clinical features, antecedent infections, CSF (Cerebrospinal fluid) analysis, and treatment responses were recorded. Samples were tested at the National Institute of Virology (NIV), Pune. Outcomes were assessed using the Hughes Functional Grading Scale. Five cases (3 male, 2 female) showed variable severity, with antecedent infections in four. NCV revealed AIDP (4 cases) and AMAN (1 case). Two patients required ventilation, one developed bradycardia, another ventilator-associated pneumonia. Intravenous Immunoglobulin (IVIG) (2 g/kg) was effective, with three achieving full recovery and two having residual weakness. Campylobacter jejuni was detected in one case. Paediatric GBS during outbreaks presents with diverse severity but responds well to IVIG. Early diagnosis and monitoring of respiratory/cranial involvement are crucial. Strengthening surveillance and investigating infectious triggers is recommended.